(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To evaluate the role of ultrasound for preoperative diagnosis of ovarian malignancy in adnexal mass. Materials & Methods: This prospective observational study was conducted on patients having adnexal mass (n-57) admitted consecutively for surgical exploration in Dept. of OB-GYN of BSMMU from January 2000 - March 2001. Abdominal ultrasonography was performed 10 days preoperatively and 5 sonographic criteria were used to calculate ultrasound score (0, 1 & 3 ). Definitive diagnosis was based on histo-pathological study . Sensitivity , specificity , positive and negative predictive values of ultrasound score to diagnose ovarian malignancy were detected . Chi square & students t test were used for statistical analysis . Results: Sensitivity , specificity , positive and negative predictive values of ultrasound score at cut-off value of 3 were 78% , 80% , 47% and 94 % respectively . Conclusion: For pre-operative diagnosis of ovarian malignancy sonographic scoring system may be introduced easily into the clinical practice where other complementary tests are not available. Combination of serum CA125 and menopausal status into ultrasound score may further improve the diagnostic accuracy in prediction of ovarian malignancy preoperatively. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 67-71